2018
DOI: 10.1016/j.energy.2018.07.208
|View full text |Cite
|
Sign up to set email alerts
|

Radiation enhanced chemical production: Improving the value proposition of nuclear power

Abstract: Nuclear power is one of the means for large-scale CO 2-free heat and electricity generation. Commercial designs, developed decades ago, have not adopted technological innovations and struggle to be cost-competitive with state-of-the-art fossil-fuel power systems. Though fuel is relatively inexpensive, nuclear power plants are expensive to build and produce only low-value electricity. One strategy to improve the process economics is to use unique characteristics of nuclear reactors to provide additional sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…There is a large amount of unused energy in the form of photon and neutron radiation that could be exploited to drive chemical processes to produce feedstock materials as a secondary product of a nuclear plant. 4 , 8 , 9 Chemical processing with radiation is not a new concept. In fact, it has been recognized for over half a century that gamma radiation is an excellent source of high-energy photons to drive photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large amount of unused energy in the form of photon and neutron radiation that could be exploited to drive chemical processes to produce feedstock materials as a secondary product of a nuclear plant. 4 , 8 , 9 Chemical processing with radiation is not a new concept. In fact, it has been recognized for over half a century that gamma radiation is an excellent source of high-energy photons to drive photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear energy provides a low-carbon alternative to reliably meet energy needs regardless of weather conditions or geological location. , It represents a key piece of a diverse energy portfolio that can effectively meet the current goals of lowering the carbon footprint of energy production while maintaining energy security. , However, nuclear energy is more expensive than many of the renewable energy generation technologies such as wind and solar, primarily due to the high capital investment required in plant construction, although modern reactors are bridging this gap. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent economic study concluded that such an integrated chemical-nuclear process could be economically feasible within a commercial nuclear reactor's design, with relatively little additional capital costs associated with the inclusion of radiochemical process. [5,6] Currently, there is still a heavy reliance on the petrochemical industry for the supply of commodity chemicals; therefore research into alternative, chemical processes that utilize waste natural feedstocks is vital to create a more sustainable future.…”
Section: Introductionmentioning
confidence: 99%
“…It is the main form of SiO 2 . In nuclear power plants, quartz can be subjected to neutron radiation when it is applied as the concrete aggregate (Field et al., 2015; Pignatelli et al., 2016; Schmeda-Lopez et al., 2018). In some cases, quartz is under the dual influence of radiation and high temperatures.…”
Section: Introductionmentioning
confidence: 99%